Serum biochemical marker of synovial tissue turnover, C1M, predicts radiological progression in early rheumatoid arthritis - Jérémie Sellam; florent Eymard; Patrick Garnero; Roland Chapurlat; Anne-C Bay-Jensen; Sofie Falkenløve Madsen (RMD Open)
Objectives To investigate whether serum C1M and C2M, biochemical markers of synovial and cartilage tissue destruction, were associated with progression of joint damage in patients with early arthritis.Methods 813 early arthritis patients (<6 months of symptoms, 82% with rheumatoid arthritis, 18% undifferentiated arthritis) from the prospective ESPOIR study were followed for 5 years. Radiographic progression was assessed using the van der Heijde Sharp score, and progression was defined as an increase of 1 or 5 unit(s) between baseline and 1 year or 5 years. Associations between baseline C1M and C2M and progression were assessed by logistic regression.Results Increased baseline continuous serum C1M levels were associated with the risk of progression at 1 year, after adjustment for age, gender and body mass index (BMI). Patients with levels in the highest quartile of C1M had an OR (95% CI) of total joint damage progression of 2.75 (1.70–4.45) compared with patients in the lowest quartile. When disease activity score 28, C reactive protein and anticyclic citrullinated peptide 2 antibodies positivity were included in the model, high C1M remained significantly associated with progression with an OR (95% CI) of 2.12 (1.06–4.23). At 5 years, C1M was significantly associated with the risk of total joint damage progression after adjustment for age, gender and BMI. There was no significant association of C2M with progression at 1 year or 5 years.Conclusions High baseline serum C1M, but not C2M, is associated with increased radiographic progression in early arthritis, independently of classical risk factors. C1M, in conjunction with other risk factors, may help identify patients at higher risk of joint damage.